Digital Marketing Strategies for Entrepreneurs in the Creative Industry - Dwi Narsih; Bambang Bernanthos (Al-Makki Publisher, 2026)
Indonesia's creative industry is a key economic driver, contributing Rp1.28 quadrillion to GDP in 2022. This research aims to analyze effective digital marketing strategies adopted by entrepreneurs within Indonesia’s creative industry and evaluate their impact on business growth and competitiveness. This research employed a qualitative research approach through literature reviews, document analysis, and case studies of creative small and medium-sized enterprises (SMEs) that have successfully implemented digital marketing practices. The findings reveal that the integration of social media platforms, e-commerce channels, and digital branding initiatives significantly enhances product visibility and customer engagement. Businesses that effectively utilize digital marketing strategies experience an average increase of 65% in product visibility and approximately 40% growth in sales performance. Platforms such as Instagram, TikTok, and local online marketplaces have become essential tools for promoting creative products and building customer relationships. The study identifies three key pillars of successful digital marketing strategies: optimization of digital platforms, development of engaging and innovative content, and utilization of consumer data analytics for decision-making. However, several challenges remain, including limited technical skills, inadequate digital literacy, and difficulties in understanding rapidly changing platform algorithms. The research concludes by recommending an integrated digital marketing framework that combines technology adoption, continuous skill development, and data-driven strategies to maximize the potential of Indonesia’s creative economy in the digital era.